Iron Porphyrin as a Cytochrome P450 Model for the Degradation of Dye - Dan-Dan Ren; Xiaoyan Lu; Li-Ping Zhou; Huanghongjun Tian; Shuang Wang; Lu-Fang Ma; Dong-Sheng Li (Molecules, 2022)
Organic dyes are widely used in the textile, biological, medical and other fields. However, a serious environmental problem has appeared because of the presence of organic dyes in industrial aqueous effluents. Thus, the efficient treatment of organic dyes in industrial wastewaters is currently in real demand. The current study investigated the oxidative degradation of the organic dye gentian violet by meso-tetra(carboxyphenyl) porphyriniron(III), [FeIII(TCPP)] as a cytochrome P450 model and iodosylbenzene (PhIO) as an oxidant at room temperature. The degradation reaction was monitored by UV–vis absorption spectroscopy via the observation of UV–vis spectral changes of the gentian violet. The results showed that the efficiency of catalyzed degradation reached more than 90% in 1 h, indicating the remarkable oxidative degradation capacity of the [FeIII(TCPP)]/PhIO system, which provided an efficient approach for the treatment of dyeing wastewater.